Integrated Internet of Things with cloud developed for data integrity problems on supply chain management - Mani Deep Karumanchi; J.I. Sheeba; S. Pradeep Devaneyan (Measurement: Sensors, 2022)
It is indeed an effort to ensure integrity of data for cloudbased Internet of Things (IoT) applications because of the inherently dynamic nature of IoT data. It is challenging to discover the integrity and authenticity of various sorts of transactions in the cloud environment as the amount of supply chain transactions grows. On massive supply chain management (SCM) data, the majority of conventional supply chain management methods or methodologies have become increasingly sophisticated. Also, the conventional integrity computation methods like the SHA family, MD5, Whirlpool, linear chaotic, etc … mostly rely on fixed random parameters with constrained hash and data sizes. To optimize these problems on the cloud-based supply chain databases, a hybrid integrity verification-based encoding and decoding technique is proposed. By interactively authenticating blockchains, the proposed method reduces IoT data integrity problems and strengthens the function of intermediary media serving as gateways. Experimental results showed that, in terms of integrity bit change, runtime, and encoding average runtime, the optimized supply chain data integrity model outperformed the traditional techniques.